Estudo das transições de fase do RbBi0,313Nd0,02 W8/3O9 submetido a variações de pressão hidrostática e temperatura - Coelho, Janilson dos Santos (2009)
Tungsten bronzes has attracted great attention owing to it is interesting physical properties. Hexagonal tungsten of the form AxWO3 (with A = K, Rb, Cs), are well know superconductors. The RbBi1/3W8/3O9 (RBW) material, belongs to the valence balanced hexagonal tungsten materials with ABxW3-xO9 stoichiometry (with A = Cs, K, Rb, Tl, and B = Bi, Nd, Ta, Zr, Sc, etc.) These materials present interesting physical properties like rich sequence of phase transitions (rich polymorphism), ferroelectric properties and second harmonic generation. Despite of the unknown structure of this system (we mean spatial symmetry), X-ray experiments suggest that Rubidium and cesium hexatungstates are isostructural with orthorhombic structure belonging possibly to Pbn21, Pbc21 or Cmm2 space group symmetry. The aim of this work was to investigate the vibrational properties of RbBi0,313Nd0,02W8/3O9 system, with special focus on the vibrational properties of this system under extreme conditions of pressure and temperature. We report in this work, a detailed study of Nd3+ doped RBW in witch we have performed light scattering high pressure experiment in the 0,0-6,6 GPa pressure range; light scattering low temperature experiment in the 300-38 K temperature range; DTA-TG experiments; photoluminescence experiments; and lattice dynamics phonons calculation in parent structure. Our results reveal that the RBW materials experiment a pressure induced structural phase transition (SPT) at around 4 GPa. This SPT is related to rotations of octahedral units around the c axis along with subtle changes in the ab pseudo hexagonal plane. Additionally we have observed two temperature induced SPT at around 200 K and 100 K. Both 4 GPa pressure induced and 200 K temperature induced SPT seems to be driven by similar mechanisms. The 100 K temperature induced SPT seems to involve more complex rotations of octahedral. Infrared and termogravimetric (TG-DTA) measurements reveal the observation of superficial water molecules in the RBW material. Termogravimetric measurements indicate that the RBW is stable up to 600 oC. We have performed Lattice dynamics phonon calculations on K0,26WO3 (RBW closely related structure with similar Raman features) in order to get insights on the vibrational properties of hexagonal tungstates. These results allowed us to interpret the transformation mechanisms of the observed pressure and temperature induced phase transitions. The lattice dynamics calculations revealed the existence of radial and tangential motions of oxygen atoms belonging to the hexagonal cavities. The tubular like modes command the dynamics of phase transitions in hexagonal tungsten systems.